The molecular mechanism study of insulin in promoting wound healing under high‐glucose conditions. Issue 9 (12th May 2019) - Wang, Lin; Yang, Bai; Jiang, Hua; Yu, Guo; Feng, Mi; Lu, Xingmei; Luo, Qiang; Wu, Hao; Zhang, Shuo; Liu, Hongchen
Abstract: Background: Wound healing is a complex process in bone development. The aim of this study was to explore the molecular mechanism study of insulin in promoting wound healing. Methods: Firstly, the acute human monocyte leukemia cell lines were induced to differentiate into macrophages. Secondly, the porphyromonas gingivalis was applied to mix with the differentiated macrophages. Thirdly, the effect of different concentrations of insulin (0 ng/mL, 5 ng/mL, 50 ng/mL, 100 ng/mL, 200 ng/mL, 500 ng/mL, and 1, 000 ng/mL) on the phagocytosis of macrophages and production of reactive oxygen species was investigated. Depending on these experiments, the optimal insulin concentration was used to treat the macrophages at different time points (0 hours and 0.5 hours) to identify the differentially expressed mRNAs. Finally, functional analysis including gene ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) and protein‐protein interaction (PPI) analysis was carried out to explore the biological function of these differentially expressed mRNAs. Results: The test of phagocytosis function and production of reactive oxygen species showed that 200 ng/mL insulin treatment had a significant influence on antibacterial and production of reactive oxygen species. In RNA sequencing, a total of 415 (245 upregulated and 170 downregulated) differentially expressed mRNAs were identified between different time points. Two important signaling pathways including endocytosis and systemic lupus erythematosus were found in the KEGG enrichment analysis. In the PPI network, several hub proteins encoded by differentially expressed mRNA including ALB, HIP1R, RAB5A, HIST1H2BJ, HIST1H3G, and HIST1H2BO were identified. Conclusion: Our work demonstrated that several differentially expressed mRNAs, such as EGR1, RAB34, ALB, HIP1R, RAB5A, HIST1H2BJ, HIST1H3G, and HIST1H2BO and two important signaling pathways including endocytosis and systemic lupus erythematosus may play important roles in the bone wound healing.